Ekologia i biologia ptaków Puszczy Białowieskiej z perspektywy czterdziestoletnich badań - Czeszczewik, Dorota; Walankiewicz, Wiesław (Leśne Prace Badawcze, 2016)
The aim of this study was to review the most important results from the last 40 years of intense ornithological research conducted in the Białowieża Forest. Furthermore, we discuss the threats that may destroy the unique ecology and characteristics of this forest. Studying the avifauna of the Białowieża Forest provides us with a good general knowledge about natural ecological conditions and relationships, which prevailed in temperate European forests in the past. The avifauna of the Białowieża Forest is characterized by features associated with primeval habitats such as the stability of communities over time, high species richness, relatively low densities, high proportion of hole-nesting birds, very high predation pressure and weak, insignificant competition interactions. This emphasizes the importance of predation, excess of nesting sites for cavity nesting birds, high abundance of food, especially for insectivorous species and fluctuation of bird population size due to rodent outbreaks (pulsed resources). The most severe threats for the avifauna of the Białowieża Forest are: rejuvenation of tree stands, removal of dead wood, fragmentation of old-growth stands, change of tree stand composition (reducing the proportion of some tree species). In order to expand our ecological knowledge about birds, we should keep the Białowieża Forest fully protected for years to come. The main priority should be the maintenance of natural processes changing the forest’s species composition.